Kesiapsiagaan perpustakaan dalam menghadapi bencana banjir - Endang Fatmawati (UIN Sumatera Utara, 2017)
This article discusses the library preparedness in the face of flood disaster. Disaster management planning is one of the important elements of a preventive corservation action. Damage to library materials caused by flood disasters is a complex phenomenon that requires serious handling. For the library is very important to prepare for the flood disaster that during the rainy season can occur at any time. Librarians should be able to participate in the preparedness of flood disasters. The goal is to prevent libraries from being flooded and minimizing damage to library materials due to flood waters. Disaster preparedness planning stages include: prevention, response, reaction, and recovery.